THE IMPACT OF ONLINE TEACHING ON THE DENTAL STUDENTS’ EXAM SUCCESS (ETIMA, 2024)
COVID-19 epidemic has changed a number of aspects in various life activities. The epidemic had the greatest impact on the education process itself. Pupils and students from classical teaching in their classrooms and lecture halls have switched to online teaching. Аt the same time, a significant effort was made by the teaching staff to adapt to the newly created situation. Aiming to assess the impact/influence of the online teaching on the success of students, we set the main goal of this research to make a comparative analysis of students' grades in the same courses in the period before the epidemic and during the implementation of online teaching.In order to fulfil the purpose of our research, an analysis was made of the grades for three courses of the study program in dental medicine - preclinical periodontology, periodontology 1 and periodontology 2 in the academic year 2018/2019 when the teaching was carried out with physical presence, 2019/2020 when the teaching it was entirely online and for 2020/2021 when a hybrid type of teaching was conducted. The pass rate of the exams and the average grades for the three most important exam sessions - June, September and February are presented.The results that we obtained within the research showed that there is significant change in terms of the pass rate of the students, as well as the average grade regarding the three courses. The pass rate has shown significant decrease, while the average grade regarding the courses increased during those years. This is solid ground for comparisons to be made with other courses, modules, faculties, even universities, towards locating the reasons for this reality. One possible and very reliable reason can be found in the fact that the change of the teaching type from classic to online and than hybrid is big and fast change for the students, that led to decrease of the pass rate, but most probably the students who passed the exam mastered the material better.
Keywords: Epidemic; students; Covid-19